دور الأسرة في إعادة انتاج العنف والتطرف - مصطفى, د.عالية فرج (Sulaimani Journal for Humanities, 2023)
This study investigates the role of the family in the production of violence and persecution, through the process of socialization and each of: wars, arrests, civil war, jihadist or armed movements, collapse of family livelihoods, rising unemployment and satellites as media tools in reproduction for violence and persecution. In this study, the researcher adhered to the descriptive analytical procedure in investigating the research problem and selected research society which is city of Sulaimani and the research sample as one hundred parents in the center of the research community, with the selection of survey forms as research tools for collecting information on the role of the family in the reproduction of violence and persecution. According to the research, it has been found that the wars and civil wars of the past 30 years that have caused changes in customs, rising unemployment and declining family livelihoods which are among the most influential factors for the role of the family in producing violence and persecution. Parental education is also considered to be a motivating factor in preventing the reproduction of domestic violence.
Keywords: Family; Violence; persistence